Health-Oriented Lifestyle as a Communicative Practice - Paholok, Olga (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article addresses the problem of transformation of the value of health into specific practices aimed at its implementation in the form of daily care ethos for health resources in modern society. The value of health embodied in the biographical experience is presented by the author as a lifestyle that focuses on health, which is a direct adaptation of the social idea of the healthy lifestyle in the form of individual lifestyle. In the paper it is proposed to define the way of life that focuses on health as a communicative activity – that one that requires a high level of self-reflection and long term. Moreover, among the important elements of this activity is its awareness as willpower, i.e. personal choice, although executed within some given social and cultural framework